Analysis of Code Switching and Code Mixing on the “Bajra” Film at the Darus Salam Modern Islamic Boarding School Gontor Ponorogo - Nurdiana Arifah; Aida Shofia (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
Darus Salam Gontor Islamic boarding school students have designed a film entitled Bajra due to the student’s creativity. In the movie, the phenomenon of code-switching and code-mixing in communication between students in the boarding school environment is found. This study aims to discover the types of code-switching and code-mixing in the Bajra film and the causes of their occurrence in the movie. This type of research is qualitative descriptive. At the same time, the data collection method uses listening/listening techniques in the Bajra film and notes essential points about the types of code-switching and code-mixing as well as the causes of what happened in the movie. The results showed that there were 3 types of code-switching in Bajra film: Metaphorical code-switching, Conversational code-switching, and situational code-switching. Meanwhile, code-mixing occurs in words, phrases, and clauses. The causes of code-switching and code-mixing are of two types, namely internal and external causes.